Perbedaan Pengaruh Short Wave Diathermy (SWD), Ultrasound (US) Dan Latihan Quadriceps Pada Klien Dengan Osteoartritis Knee - Dwi Purwantini; Intan Febby Setiani (Jurnal Keperawatan Muhammadiyah, 2022)
Objective:   to compare the intervention of SWD/US and quadriceps exercise with an electrotherapy package in reducing pain in patients with knee OA . Methods: The method of research is  quasi-experimental with pre and post test control group design. Subjects of the study were 52 clients with knee OA, aged 29-88 years divided into 2 groups. The experimental group was given SWD/US and quadriceps exercises, while the control group given  electrotherapy packages. The data is colleted using the Numeric Pain Rating Scale (NPRS).Results:  The research data shows that p = 0.00 Ho is rejected and Ha is accepted, so the hypothesis states that the intervention of SWD/US and quadriceps exercises as well as the provition of electrotherapy packages had an effect on decreasing the value of the NPRS in klien with osteoathritis knee. Conclusion:  The prove that  adding quadriceps strengthening exercises provides a more significant pain reduction in clients with knee OA